2018
DOI: 10.13075/ijomeh.1896.01166
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of occupational exposure to gaseous peracetic acid

Abstract: Objectives: In order to assess short-term exposure to peracetic acid (PAA) in disinfection processes, the Authors compared 4 industrial hygiene monitoring methods to evaluate their proficiency in measuring airborne PAA concentrations. Material and Methods: An active sampling by basic silica gel impregnated with methyl p-tolyl sulfoxide (MTSO), a passive solid phase micro-extraction technique using methyl p-tolyl sulfide (MTS) as on-fiber derivatization reagent, an electrochemical direct-reading PAA monitor, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Recent full-shift measurements of PAA within hospital environments indicate that workers experienced exposure symptoms in response to low concentrations of PAA in the air during full work shifts. Such findings support the need for additional full-shift TWA measurements to document the impact of longer exposures on workers. , Current published PAA methods have been developed based on a 15 min sampling period, collecting 15 L of air; however, the performance of these methods with longer sampling periods has not been established. …”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Recent full-shift measurements of PAA within hospital environments indicate that workers experienced exposure symptoms in response to low concentrations of PAA in the air during full work shifts. Such findings support the need for additional full-shift TWA measurements to document the impact of longer exposures on workers. , Current published PAA methods have been developed based on a 15 min sampling period, collecting 15 L of air; however, the performance of these methods with longer sampling periods has not been established. …”
Section: Discussionmentioning
confidence: 91%
“…Scalability of the sampling time was also preliminarily assessed through a series of experiments wherein sampling occurred for 15 min at a rate of 1 L/min using chambers containing 80 L of PAA-spiked air (800 ppb, 199 μg), which is reflective of current PAA testing methods. The average of four 15 min replicates from three separate chambers is shown in Table . Across the three chambers, the amount of PAA recovered differed minimally from the 37 μg anticipated from a 15 L sample at 800 ppb, as the average absolute bias estimate was 7.2%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a 2017 study by Casey et al, which evaluated ocular exposure to disinfectants with peracetic acid in their composition, eye irritation was the most described symptom in 401 exposed patients, with other symptoms including tearing, burning, and ocular discomfort [ 5 ]. Other studies have shown that peracetic acid can cause damage to the mucosa of the upper respiratory tract, the conjunctiva, and the skin [ 2 , 4 ]. These data corroborate the present report, as the patient reported burning in the eyes, in addition to conjunctival hyperemia, which pointed to a local inflammation process, also demonstrated by ciliary injection and punctate keratitis, which indicated the involvement of the corneal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of this acid requires care because direct exposure can cause severe burns, allergies, and damage to the ocular mucosa, skin, and respiratory tract, with exposure at 4.67 mg/m 3 for 12 minutes causing minor burns and 6.23 mg/m 3 for 60 minutes causing severe mucosal damage. Exposure to concentrations greater than 0.35% peracetic acid is related to irreversible damage to the eye, but at concentrations less than 0.35%, the damage may be reversible, depending on the time of exposure [ 2 , 4 ]. Therefore, the present study aimed to report the case of a patient who had ocular contact with peracetic acid that manifested as visual complaints followed by evolution to ophthalmologic damage.…”
Section: Introductionmentioning
confidence: 99%